2008
DOI: 10.1016/j.cub.2007.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Cargo-Selected Transport from the Mitochondria to Peroxisomes Is Mediated by Vesicular Carriers

Abstract: Mitochondria and peroxisomes share a number of common biochemical processes, including the beta oxidation of fatty acids and the scavenging of peroxides. Here, we identify a new outer-membrane mitochondria-anchored protein ligase (MAPL) containing a really interesting new gene (RING)-finger domain. Overexpression of MAPL leads to mitochondrial fragmentation, indicating a regulatory function controlling mitochondrial morphology. In addition, confocal- and electron-microscopy studies of MAPL-YFP led to the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
523
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 492 publications
(554 citation statements)
references
References 21 publications
20
523
0
4
Order By: Relevance
“…Although the unregulated disruption of the mitochondrial membrane is ordinarily implicated in cell death and apoptosis, there is increasing evidence that regulated vesicular transport may occur between mitochondria and other cellular organelles. For example, iron may be transported to the mitochondria via endosomes (32), and more recent studies have shown that membranous vesicles bud off from mitochondria, transporting fatty acids to the peroxisome (33). The data presented here suggest a role for mitochondria in the trafficking of ions or clusters of calcium and phosphate ions to the extracellular space, facilitating mammalian mineralization.…”
Section: Resultsmentioning
confidence: 62%
“…Although the unregulated disruption of the mitochondrial membrane is ordinarily implicated in cell death and apoptosis, there is increasing evidence that regulated vesicular transport may occur between mitochondria and other cellular organelles. For example, iron may be transported to the mitochondria via endosomes (32), and more recent studies have shown that membranous vesicles bud off from mitochondria, transporting fatty acids to the peroxisome (33). The data presented here suggest a role for mitochondria in the trafficking of ions or clusters of calcium and phosphate ions to the extracellular space, facilitating mammalian mineralization.…”
Section: Resultsmentioning
confidence: 62%
“…S6 and Dataset S1). Human MAPL is localized to both mitochondria and peroxisomes, but its function in peroxisomes is unclear (57). It is possible that this family of E3 enzymes targets to and regulates the biogenesis of multiple organelles across diverse species.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of cells having POX1 mRNA localized to mitochondria might stem from the fact that Oxa1-RFP-labeled mitochondria fill a substantial volume of the cell. Alternatively, evidence for cargo-selective transport between mitochondria and peroxisomes has been reported (20), indicating that these organelles are in close contact. Thus, mPPs may appear juxtaposed to mitochondria, without necessarily being associated with the mitochondrial membrane.…”
Section: Mrnas Coding For Specific Peroxisomal Matrix Proteins Localimentioning
confidence: 99%